Study of improving the quality of learning in an effort to improve the quality of elementary school education - Ketut Susiani; I Wayan Suastra; Ida Bagus Putu Arnyana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
Quality education is education that is able to carry out the process of maturation of student quality developed by liberating students from ignorance, incompetence, helplessness, untruth, dishonesty, and from poor morals and faith. This study aims to analyze the quality of education in Buleleng Regency with a meta-analysis approach. The subjects of this study are researchers and research reports, data analysis begins with categorizing each research in accordance with its research paradigm and the central issues raised, and then the results of all studies are compared according to their categories. The results showed that student learning outcomes are strongly influenced by the quality of teachers or teaching staff. And the quality of teaching can be done by developing innovative learning models. If educators are able to improve performance related to improving classroom management and the learning process by participating in training on various innovative learning, then the quality of education and the quality of graduates will be able to compete in the global era